If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2(-2) = 8 Multiply 2 * -2 x + -4 = 8 Reorder the terms: -4 + x = 8 Solving -4 + x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + x = 8 + 4 x = 8 + 4 Combine like terms: 8 + 4 = 12 x = 12 Simplifying x = 12
| 12+2x=4-x | | 3(t-2)=9(t-2) | | 5(x-5)=(14-4) | | 20x+5x-10=90 | | 4-w=3w | | 2r+1=5-11 | | .96y-0.79=0.21y+0.46 | | 6x^2-x+1=3 | | 3x-2x=14+3x | | 6.8y-2.4y=88 | | 2x=5x-2 | | 0.5x+6=x^2+12x | | 0.5x+6=x | | 3p^2-10=-7 | | 4x^2-7x+7=5x+2 | | 2y+9=3 | | 4x^2+3x-729=0 | | x^2+4x-7=-3x+1 | | x^2+13x+37=1 | | 3(x-5)-20=8x-10 | | 8y+4=4 | | 6(9-b)=-1 | | lnx=3.19 | | 5+ln(x+2)=4 | | ln(x)=3.19 | | -0.2(34.3+3x)=0.1x | | 7c-(-8)-2c=17 | | (5x-1)2=22 | | -5x-4.2=121 | | 15.3=67-y | | a-x=0.1 | | -5x-x=-3 |